2008
DOI: 10.1016/j.juro.2008.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Model for Predicting Survival After Palliative Urinary Diversion for Ureteral Obstruction: Analysis of 140 Cases

Abstract: The current stratification model may represent a useful tool for clinicians treating patients with ureteral obstruction due to advanced cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
91
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 9 publications
3
91
0
8
Order By: Relevance
“…A recent study reviewed all such patients at an institution who were treated with either ureteral stenting or percutaneous nephrostomy tubes. 31 In this group, the median overall survival was only 96 days. Therefore, the various treatment options available must improve quality of life to be of a significant benefit.…”
Section: What Is the Prognosis In Obstructive Uropathy?mentioning
confidence: 80%
“…A recent study reviewed all such patients at an institution who were treated with either ureteral stenting or percutaneous nephrostomy tubes. 31 In this group, the median overall survival was only 96 days. Therefore, the various treatment options available must improve quality of life to be of a significant benefit.…”
Section: What Is the Prognosis In Obstructive Uropathy?mentioning
confidence: 80%
“…In this study, it was shown that patients with three or more events related to malignant dissemination (for instance, liver metastasis or ascites), low degree of hydronephrosis, and low serum albumin before diversion had the shortest survival time and should therefore probably be spared the burden of the nephrostomy tube. 15 The second question to be answered once a decision has been made to proceed with urinary diversion is: ''Which is the best available option for achieving this goal?'' The urologist has to judge the best means of diversion, taking into consideration the patient's current status, quality-of-life issues, predicted survival, and cost.…”
Section: Should Obstruction Be Relieved and When?mentioning
confidence: 99%
“…PCN placement for extrinsic ureteral compression has remarkable technical success rates (96% to 100%) compared with retrograde stent placement in reversing upper-tract obstruction. 3,15,34,36,[41][42][43][44][45][46] Endoscopic placement of a stent in the setting of advanced malignancy has been considered technically demanding or even impossible in cases of extensive pelvic disease. Results from early series reported very low success rates for primary retrograde placement of a stent, rarely exceeding 50%.…”
mentioning
confidence: 99%
“…4,5 Despite the controversy in the management of this condition and the accepted poor prognosis, most patients receive percutaneous nephrostomy tubes (PNTs), retrograde ureteric stents or both. 1,[6][7][8] In contrast, those with benign causes have cause-specific interventions and do well. We sought to describe the etiology, management and outcome in a contemporary cohort of patients with ARKI secondary to BUO who had malignant or benign disease and to compare them to a similar historical group.…”
Section: Introductionmentioning
confidence: 99%